Suistainability of Small Scale Capture Fisheries in Banggai Laut Waters, Indonesia - Putra, Aswad Eka; Mansyur, Kasim; Sulistiawati, Dwi; Nurdin, Muh Saleh (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2021)
Small scale capture fisheries is one of the leading sectors that drive the economy of Banggai Laut Regency. Fishing technology improved related to fishing efforts has an effect on the preservation of fish stocks resource in the area that it required management efforts. This study aims to determine the sustainability status of small scale fisheries in Banggai Laut Regency based on ecological, fishing technology, social and economic dimensions. The research was conducted from September to December 2017 in seven sub-districts in Banggai Laut Regency. In determining the sustainability status of each dimension, the Rapfish (Rapid Appraisal for Fisheries Sustainability) approach is used. Furthermore, in determining the attributes that had an influence on the sustainability performance of small scale capture fisheries, a leverage analysis is carried out. The results showed that the highest sustainability index was the economic dimension of 75.57 (good), the ecological dimension of 59.25 (good), and the lowest was the social dimension of 22.95 (very bad), the dimension of fishing technology was 22.62 (very bad). Remedial measures that must be taken to improve sustainability performance include improving law enforcement facilities and infrastructure at sea and empowering supervisory officers, limiting excessive use of FAD, providing subsidies to small scale fisheries, and regulating fishing areas between local fishermen and Andon fishermen.